The Role of Firm Size in Moderating the Effects of Liquidity, Leverage, and Profitability on Firm Value (A Case Study of Energy Sector Companies on the Indonesia Stock Exchange, 2015–2024) - Ranisania Arianda Djaha; Paulina Y. Amtiran; Efandri Agustian; Petrus E. De Rozari (Asian Journal of Management Analytics, 2026)
This study examines the role of firm size in moderating the effect of liquidity, Leverage, and profitability on firm value in energy sector companies listed on the Indonesia Stock Exchange during 2015–2024. A quantitative approach was applied using secondary data from annual financial statements. The analytical methods included panel data regression and Moderated Regression Analysis (MRA). The results indicate that Leverage significantly affects firm value, while liquidity and profitability have no significant effect. Simultaneously, liquidity, Leverage, and profitability significantly influence firm value. Firm size strengthens the effect of Leverage on firm value, but does not moderate the effects of liquidity and profitability. These findings imply that capital structure remains an important determinant of firm value in the energy sector.